Penetapan Kadar Formalin Pada Mie Basah Yang Beredar Di Pasar Peunayong Kota Banda Aceh Secara Spektrofotometri Visible - Syarifah Nadia; Dea Anggreini; Siti Rahmi Ningrum; Supran Hidayat Sihotang; Ernawaty Ginting; Debi Meilani (Pusat riset dan Inovasi Nasional, 2025)
Formalin is a 37% formaldehyde solution in water, commonly misused as a food preservative despite its toxicity and prohibition in food products. This study aimed to determine the presence and levels of formalin in wet noodles sold at Peunayong Market, Banda Aceh, using visible spectrophotometry. A descriptive design was applied to three randomly selected samples. Qualitative tests using multiple reagents (Schiff, Schryver, KMnO₄, and a test kit) showed negative results for formalin presence. However, quantitative analysis with Spectroquant Prove 300 revealed that all samples contained formalin levels exceeding the acceptable standard. The concentrations ranged from 0.7433 mg/L to 0.8766 mg/L, indicating that the products are unsafe for consumption. These findings underline the need for stricter monitoring and improved food safety awareness among producers and consumers in traditional markets.